Grandmothers and Non-grandmothers in the Polish Labor Market: The Role of Family Issues. (August 2019) - Wilińska, Monika; Grzenda, Wioletta; Perek-Białas, Jolanta
Drawing on the debates regarding work–family reconciliation in later life, we examine the extent to which the labor market position of grandmothers and nongrandmothers can be explained by their varied family situations. The data for this study comes from the Generations and Gender Survey for Poland and includes 5, 999 women aged 45+ years. We use multinominal logistic regression models to explore the link between different family situations and labor market withdrawal into unemployment, sick/disability leave, and retirement. Our results indicate that neither caring for older parents nor living with children has significant effects on women's labor activity. However, living with a disabled person reduces the chances for women's employment significantly. In addition, women who have grandchildren have lower chances for being employed as compared with those without grandchildren. We discuss these findings in relation to work–family balance policies and research.